Three-Dimensional-Printed Mechanical Transmission Element with a Fiber Bragg Grating Sensor Embedded in a Replaceable Measuring Head - Piotr Lesiak; Konrad Pogorzelec; Aleksandra Bochenek; Piotr Sobotka; Karolina Bednarska; Alicja Anuszkiewicz; Tomasz Osuch; Maksymilian Sienkiewicz; Piotr Marek; Michał Nawotka; Tomasz R. Woliński (Sensors, 2022)
Compliant mechanisms have gained an increasing interest in recent years, especially in relation to the possibility of using 3D printers for their production. These mechanisms typically find applications in precise positioning systems of building robotic devices or in sensing where they can be used to characterize displacement. Three-dimensional printing with PLA materials allows fiber optic-based sensors to be incorporated into the structures of properly designed compliant mechanisms. Therefore, in this paper, an innovative technology is described, of a Fiber Bragg Grating (FBG) sensor embedded in a measuring head which was then inserted into a specially designed mechanical transmission element. The shape of this element is based on clippers that allow to freely modify the amplification of displacement amplitude so that the FBG sensor always works in the most optimal regime without any need to modify its external dimensions. Flexural sensitivity of the replaceable measuring head equal to 1.26 (mε/mm) can be adapted to the needs of the flexure design.